Effect of an isocaloric carbohydrate-protein-antioxidant drink on cycling performance - Romano-Ely, B. C.; Todd, M. K.; Saunders, M. J.; St. Laurent, T. (Medicine & Science in Sports & Exercise, 2006)
Purpose: Fourteen male cyclists were studied to compare the effect of carbohydrate-protein-antioxidant beverage (CHOPA) to an isocaloric carbohydrate-only (CHO) beverage on time to fatigue and muscle damage.